Is the extreme within-population genome size variation real in Spodoptera frugiperda? - Karine Durand; Kiwoong Nam (PLoS ONE, 2025)
Genome size variation is one of the main topics in evolutionary genomics. Recent studies in Spodoptera frugiperda (Insect; Lepidoptera) reported very striking results, including large genome size differences, up to a twofold variation within populations, with the existence of 1.37 Gb of non-reference genome sequences, which is 2.5 times larger than the reference genome, 544 Mb in size. These reports raise the question of whether such extreme genome size variations within populations can be biologically realistic. To evaluate these results, we analyzed reference genome assemblies and resequencing datasets from multiple independent studies, including those from the original research. We observed that high-quality reference genomes consistently range from 380 Mb to 390 Mb, aligning closely with flow cytometry measurements. The genome size estimates using k-mer-based approaches from field-collected samples across four independent studies suggest that extensive genome size variation within S. frugiperda is unlikely to occur. Additionally, genome size appears to have remained stable for at least 15.89 million years in the ancestral lineage of S. frugiperda. Taken together, these results do not support the existence of extreme genome size variation in S. frugiperda, emphasizing the need for careful validation.